EVALUASI MUTU PROTEIN BISKUIT YANG MEMANFAATKAN BLONDO DAN DIPERKAYA DENGAN TEPUNG IKAN GABUS - Iswahyudi Iswahyudi; Rimbawan Rimbawan; Evi Damayanthi (UHAMKA PRESS, 2016)
ABSTRACTThe objective of this research was to analyze the true digestibility (TD), biological value(BV), and net protein utilization (NPU) of biscuits. The research used 25 rats of Spraguedawley aged between 29-32 days. The research was conducted in two stages, adaptation andintervention period. The period of adaptation was conducted for 4 days by providing thestandard feed (AOAC 1995) and aquades ad libitum. The period of intervention was began byclassifying 25 rats into 5 groups: group A (fed with standard biscuit feed), group B (fed withblondo biscuit feed), group C (fed with blondo + snakehead biscuit feed), group K1 (fed withnon-protein feed), and group K2 (fed with casein feed). Intervention was carried out for 10days. During the intervention, a given amount of feed, remaining feed, urine, and feces werecollected and weighed for analysis purposes. Data were analyzed using Analysis of Variants(ANOVA). If the results of ANOVA showed signifcant differences (p<0,05), then followed byDuncan’s test with 5% confdence interval. The results showed that total of feed intake, weight gain, and Feed Conversion Effciency (FCE) were signifcantly different (p<0,05). The value of the TD, BV, and NPU of casein group, standard biscuit group, blondo biscuit group and blondo+ snakehead biscuit group were not signifcantly different (p>0,05).